Do senso de lugar no aprendizado da arte: uma experiência docente realizada no ensino fundamental ciclo II da Escola Estadual Governador André Franco Motoro em São Lourenço da Serra, SP - Montenegro, Maria Regina Pacheco de Medeiros (2009)
This dissertation is an account of a teaching experience held in the subject of Arts in a State Public School in São Paulo, in 2007. It aims at investigating the aspects related to the concept of sense of place used together with the pedagogical situations performed. In order to do so, some relevant aspects related to the theme of place , such as the school location and the territoriality from the Arts teaching point-of-view. Said considerations have come up in this paper due to didactic actuation in context. The sense of place approach is expressed as a transforming ideal, in the sense it suggests an appropriation of the environment where we live and performs a trajectory of expressive intimacy turning a location into a place. It was evidenced that the complexity of the sense of place content is due to the diversity of areas of knowledge, to which one is exposed, and the boldness of approaching the topic through teaching experience, resulting in an inviting introduction to a vast territory.